Correlation of Vitamin D level with severity of Coronary Artery Disease(CAD) in patients of Acute Coronary Syndrome(ACS) in a Tertiary Care Centre in Western India (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background : Vitamin D deficiency (VDD) is a widespread problem in developing countries. Recentstudies have shown association of Vitamin D deficiency with atherosclerosis and Coronary artery disease.This study was conducted to assess the relationship between Vitamin D and the severity of coronary arterydisease (CAD) in patients undergoing coronary angiography.Materials and methods: Consecutive patients who underwent coronary angiography for acute coronarysyndrome or effort angina were included in a descriptive cross-sectional study and their Vitamin D levelwas measured. CAD was defined as at least one vessel stenosis >50% on coronary angiography. Vitamin Dlevels were correlated to the CAG findings as to the severity and number of vessels involved and also to thetraditional CAD risk factorsResults: Vitamin D Deficiency was noted in 70.72% of the population in the study. Patients were classifiedas normal Vitamin D level(> 30ng/ml), Vitamin D insufficiency (20-30ng/ml) and Vitamin D Deficiency(
Keywords: Vitamin D, Coronary artery disease, Coronary angiography